PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE BERBANTUAN MEDIA BIG BOOK TERHADAP KETERAMPILAN MENULIS KREATIF PANTUN - Margareta Oktavia Ningsih; Dessy Wardiah; Aldora Pratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Writing skills are an ability possessed by a person and a way or activity where the writer can convey and express ideas, thoughts, which the writer will convey through typed or written writing directly, so that the reader can know the intent and purpose of the written sentence. This study aims to determine the effect of the Think Talk Write learning model assisted by Big Book media on creative pantun writing skills. The method used is an experimental research method (quantitative method) with a true-experimental design in the form of a posttest only control design. There are two variables, namely variable X (Think Talk Write Model Assisted by Big Book Media) and variable Y (Pantun Writing Skills). The population in this study were all fifth-grade students of SD Negeri 101 Palembang, totaling 56 students. The data collection technique used an essay test. The instrument for measuring creative pantun writing skills used a Posttest in the form of essay test questions. The data analysis technique used the t-test (independent sample t-test) after the normality and homogeneity tests were carried out. The average value of the control class posttest was 58,50 and the experimental class posttest was 73,07 with a 2-tailed sig value of 0,025 < 0.050, so there is an influence of the Think Talk Write learning model assisted by Big Book media on the creative writing skills of pantun of class V students of SD Negeri 101 Palembang.